Coupled Scalar Fields Oscillons and Breathers in Some Lorentz Violating Scenarios - R. A. C. Correa; A. de Souza Dutra (Advances in High Energy Physics)
We discuss the impact of the breaking of the Lorentz symmetry on the usual oscillons, the so-called flat-top oscillons, and the breathers. Our analysis is performed by using a Lorentz violation scenario rigorously derived in the literature. We show that the Lorentz violation is responsible for the origin of a kind of deformation of the configuration, where the field configuration becomes oscillatory in a localized region near its maximum value. Furthermore, we show that the Lorentz breaking symmetry produces a displacement of the oscillon along the spatial direction; the same feature is present in the case of breathers. We also show that the effect of a Lorentz violation in the flat-top oscillon solution is responsible by the shrinking of the flat-top. Furthermore, we find analytically the outgoing radiation; this result indicates that the amplitude of the outgoing radiation is controlled by the Lorentz breaking parameter, in such a way that this oscillon becomes more unstable than its symmetric counterpart; however, it still has a long living nature.